Perancangan sistem pembelajaran online learning (e-learning) pada Mts Al manshuriyah - fajardanu setyawan; Samsoni Samsoni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Information Technology has played an important role as a medium of information and communication in the field of education, one of which is in the Academic Management of Schools. In the world of educational technology, it is not only related to the internet but can also be seen from the system or how to teach in schools. MTS Al-Manshuryah is one of the educational institutions that works to create students who have good morals and achievements based on faith and piety. For now, the facilities provided by the school are very helpful for students in their learning process. However, in addition to complete facilities, MTS Al-Manshuryah still has a fairly complex weakness in distance learning. To reduce these weaknesses, MTS Al-Manshuryah needs to have a system that can facilitate teachers and students in the teaching process remotely. The methodology used in designing this information system uses Waterfall, this methodology can be used as a methodology to analyze and design a WEB-based e-learning online learning system at MTS Al-Manshuryah The results of this study indicate that the use of a web-based e-learning online learning system has accommodate With the existence of a website-based online learning learning system, the teaching and learning process can still run even if the teacher or student is unable to attend. San With the online learning system based on the website of teachers and students, there is no time limit for studying